Relationship Between Plasma Osteopontin and Arginine Pathway Metabolites in Patients With Overt Coronary Artery Disease - Moschetta, Donato; Di Minno, Matteo Nicola Dario; Porro, Benedetta; Perrucci, Gianluca L.; Valerio, Vincenza; Alfieri, Valentina; Massaiu, Ilaria; Orekhov, Alexander N.; Di Minno, Alessandro; Songia, Paola; Cavalca, Viviana; Myasoedova, Veronika A.; et al. (Frontiers in Physiology, 2020)
Introduction: Osteopontin (OPN) is involved in ectopic calcification. Its circulating form is upregulated in coronary artery disease (CAD) patients. Circulating OPN levels positively correlate with oxidative stress, one of the major triggers of endothelial dysfunction. Endothelial dysfunction is, in turn, associated with reduced nitric oxide (NO) bioavailability due to the impaired arginine pathway. The aim of this study was to better understand the correlations between OPN, oxidative stress markers, and the arginine pathway metabolites. Methods and Results: ELISA and mass spectrometry techniques have been used to evaluate circulating OPN and arginine pathway/oxidative stress metabolites, respectively, in twenty-five control subjects and thirty-three patients with overt atherosclerosis. OPN positively correlates with 2,3-dinor-8isoPGF2a levels (p=0.02), ornithine (p=0.01), ADMA (p=0.001), SDMA (p=0.03), and citrulline (p=0.008) levels only in CAD patients. In addition, citrulline positively correlated with ADMA (p=0.02) levels, possibly as result of other sources of citrulline biosynthetic pathways. Conclusions: The association between OPN and impaired arginine/NO pathway could play a role in the inhibition of endothelial NO synthase (eNOS) and/or in the arginase activation in the context of CAD patients. However, further studies are needed to verify the cause-effect relationship between OPN, oxidative stress, and arginine/NO pathway dysregulation.